Improving the convergence time of DCTCP to reduce the completion time of short flows: a congestion window‐based method. Issue 5 (1st September 2017) - Wu, Hangxing; Wang, Hongbin; Wan, Yadong; Zhang, Ming
Abstract : Data Center Transmission Control Protocol (DCTCP) is an excellent transmission control protocol for data centre network (DCN). Although DCTCP can achieve the high throughput and stability, it trades off the convergence time. It takes a long time for a new flow to increase its congestion window ( cwnd ), which greatly increases the completion time of some delay sensitive short flows, such as query traffic, short messages existing extensively in DCN. An improved DCTCP (IDCTCP) is proposed to improve the convergence of DCTCP. IDCTCP utilises the receive window field in TCP header to communicate sender's current cwnd to a switch. The switch only marks the packets with large cwnd . So the flows with small cwnd are protected and can increase their cwnd quickly, which can effectively improve the convergence time of DCTCP. As a result, the short flows completion time (SFCT) can be reduced. The performance of IDCTCP has been validated by NS2 simulations.